Formation of Optimal Field Crop Structure on Leased Lands of Agricultural Enterprises - BOHACH, Larysa; HERAIMOVYCH, Violeta; HUMENIUK, Iryna; NAHORNYI, Vitalii; GERASYMENKO, Nataliia (Journal of Advanced Research in Law and Economics; Vol 10 No 6 (2019): JARLE Volume X Issue 6(44) Fall 2019, 2019)
The scientific article is devoted to the actual issue of formation of the optimal field crop structure on the leased lands of agricultural enterprises. The proposals for the field crop structure optimization are developed, this will facilitate the increase of the field crop production efficiency, and, accordingly, the level of leased land use. The article is aimed at studying the problem of development of land-lease relations in agricultural enterprises, by way of optimization of leased land use, which will lead to the agricultural production increase. To study and determine the organizational and economic principles of the leased land use optimization, which will lead to the agricultural production increase, and increase the overall performance of agricultural enterprises activity. To optimize the use of leased land resources, which will increase both agricultural production and agricultural enterprises operational efficiency, we have developed a corresponding economic and mathematical model based on the simplex method. The study referred to the period 2014 – 2016. The study of optimal acreage formation and proper use of leased land in agricultural enterprises is an urgent task that requires an immediate solution.